2017
DOI: 10.1504/ijsrece.2017.084354
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stock market and macroeconomic variables on real estate prices dynamics: evidence from Saudi Arabia

Abstract: Abstract:To enhance portfolio return and achieve diversification, Saudi investors have long been seeking opportunities in real estate markets since the crash of Saudi stock market on February 2006. The aim of this paper is to explain the determinants of real estate price dynamics in the case of Saudi Arabia. Using monthly data from January 2008 to December 2012, we examine the impact of key monetary policy and macroeconomic variables, including money supply growth, inflation rates and interest rate, on the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…This finding on the GDP supports the argument in the Dipasquale and Wheaton (1996) model. The findings on the GDP are also in line with Ouma (2015), Égert and Mihaljek (2007) and Njaramba et al (2018) who concluded in their studies that an increase in the GDP has a significant impact on the real estate prices.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This finding on the GDP supports the argument in the Dipasquale and Wheaton (1996) model. The findings on the GDP are also in line with Ouma (2015), Égert and Mihaljek (2007) and Njaramba et al (2018) who concluded in their studies that an increase in the GDP has a significant impact on the real estate prices.…”
Section: Resultssupporting
confidence: 87%
“…This finding on the GDP supports the argument in the Dipasquale and Wheaton (1996) model. The findings on the GDP are also in line with Ouma (2015), Égert and Mihaljek (2007) and Njaramba et al (2018) who concluded in their studies that an increase in the GDP has a significant impact on the real estate prices. An increase in the inflation rates means that the people spend more on other commodities such as foodstuff and therefore the money available for housing purchases is limited thereby…”
Section: Long-run Effects Of Macroeconomic Factorssupporting
confidence: 87%
See 1 more Smart Citation
“…The study focuses on the determinant of real estate prices dynamics in the case of Saudi Arabia. The regression shows that stock market returns move with real estate prices in bullish markets (Dohiman, 2017). How real estate investment affects Chinese economic growth which has a positive impact on economic growth both at national and regional levels.…”
Section: Review Of Literaturementioning
confidence: 99%